Rhabdosoma minor Fage 1954 - Gasca, Rebeca; Hendrickx, Michel E. (Zenodo, 2022)
Rhabdosoma minor Fage, 1954 Rhabdosoma minor Fage, 1954: 661; Brusca, 1981: 12 (list), 32 (key), fig. 21e; Siegel Causey, 1982: 350 (key), 359; Vinogradov et al. , 1996: 536 (key), 541‒544, fig. 234; García Madrigal, 2007: 158 (list); Gasca, 2009: 89 (tab. 1); Lavaniegos & Hereu, 2009: 152 (appendix); Gasca et al ., 2012: 126 (tab. 1), 127‒136 (passim); Lavaniegos, 2014: 5 (tab. 1); Valencia et al ., 2013: 52 (tab. 1); Zeidler, 2016: 78‒79 (passim), fig. 36C, 80 (key); Violante-Huerta et al ., 2021: 81 (tab. 1), 85‒86, fig. 2D. Material examined . 9F in four localities (Fig. 3). TALUD I. St. 6 (23°15’54”N, 107°31’12”W), December 12, 1989, 1F, BO from surface to ca. 200 m (TD, 1550 m) (ICML-EMU-12965). TALUD VI. St. 7 (22°21’39”N, 107°01’42”W), March 14, 2001, 6F, MN from surface to 1305 m (TD, 2100 m) (ICML-EMU-12966); St. 29 (25°16’24”N, 109°24’54”W), March 16, 2001, 1F, MN from surface to 1440 m (TD, 2080 m) (ECOSUR-10560); St. 36(2) (25°53’15”N, 110°10’10”W), 1F, MN, from surface to 1360 m (TD, ca. 2000 m) (ICML-EMU-12967). Distribution . Circumtropical. In the eastern Pacific from California to Costa Rica and Panama (García Madrigal 2007, Valencia et al . 2013, Violante-Huerta et al . 2021, this study). Remarks . The telson length of the specimens identified herein was variable, but always around 1/2 the length of the double urosomite. In some specimens, the telson could reach (as described for this species) or not the tip of the uropod 2 (as in R. brevicaudatum ). However, none of the examined specimens possess a small segment in the tip of the callynophore, a character specific of R. brevicauda tum. Males of this species are not kown. The exact position of the type locality is unknown. Based on the morphological similarity and the allopatric distribution between R. brevicaudatum and R. minor , Vilogranov et al . (1992) suggested that they could be considered as subspecies. Zeidler (1996: 69), however, stated that “It is sometimes difficult to distinguish between these two species as the length of the telson seems to vary, and Vinogradov et al . (1982) suspect that they may even be synonymous. However, in all the specimens that were examined the first antennae of R. brevicaudatum consist of the basal article, callynophore, and one small terminal article while in R. minor the first antennae are like those of female R. whitei , consisting of just the basal article, and callynophore, although, the callynophore seems to have an incomplete article proximally, thus approaching the condition found in female R. armatum ”. Rhabdosoma minor was reported as a rare species in the Gulf of California by Siegel-Causey (1982), although it was found in the northern, central and southern Gulf. It has also been reported for the Mexican portion of the California Current by Lavaniegos & Hereu (2009) and Lavaniegos (2014). Our data show a rather wide distribution pattern in the Gulf of California (Fig. 3), but with few specimens. : Published as part of Gasca, Rebeca & Hendrickx, Michel E., 2022, Pelagic amphipods (Crustacea: Amphipoda: Hyperiidea) in western Mexico. 7 Superfamily Platysceloidea. Family Oxycephalidae, pp. 219-236 in Zootaxa 5105 (2) on pages 226-227, DOI: 10.11646/zootaxa.5105.2.3, http://zenodo.org/record/6332529 : {"references": ["Fage, L. (1954) Les Amphipodes pelagiques du genre Rhabdosoma. Comptes rendus hebdomadaire des Seances de l'Academie des Sciences, Paris, 239, 661 - 663.", "Brusca, G. J. (1981) Annotated keys to the Hyperiidea (Crustacea: Amphipoda) of North American coastal waters. Allan Hancock Foundation Technical Reports, 5, 1 - 76. https: // doi. org / 10.2307 / 1547968", "Lavaniegos, B. E. & Hereu, C. (2009) Seasonal variation in hyperiid amphipod abundance and diversity and influence of mesoscale structures off Baja California. Marine Ecology Progress Series, 394, 137 - 152. https: // doi. org / 10.3354 / meps 08285", "Gasca, R., Franco-Gordo, C., Godinez-Dominguez, E. & Suarez-Morales, E. (2012) Hyperiid amphipod community in the Eastern Tropical Pacific before, during, and after El Nino 1997 - 1998. Marine Ecology Progress Series, 455, 123 - 139 https: // doi. org / 10.3354 / meps 09571", "Lavaniegos, B. E. (2014) Pelagic amphipod assemblage associated with subarctic water off the West Coast of the Baja California Peninsula. Journal of Marine Systems, 132, 1 - 12. https: // doi. org / 10.1016 / j. jmarsys. 2013.12.012", "Valencia, B., Lavaniegos, B., Giraldo, A. & Rodriguez-Rubio, E. (2013) Temporal and spatial variation of hyperiid amphipod assemblages in response to hydrographic processes in the Panama Bight, eastern tropical Pacific. Deep-Sea Reseach I, 73, 46 - 61. https: // doi. org / 10.1016 / j. dsr. 2012.11.009", "Zeidler, W. (2016) A review of the families and genera of the superfamily Platysceloidea Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. Zootaxa, 4192 (1), 1 - 136. https: // doi. org / 10.11646 / zootaxa. 4192.1.1", "Violante-Huerta, M., Morales-Ramirez, A. & Sanvicente-Anorve, L. (2021) Anfipodos pelagicos (Amphilochidea, Hyperiidea y Senticaudata) del Pacifico de Costa Rica: nuevos registros y una lista de especies actualizada. Revista de Ciencias Marinas y Costeras, 13 (1), 77 - 97. https: // doi. org / 10.15359 / revmar. 13 - 1.5", "Siegel-Causey, D. (1982) Factors determining the distribution of hyperiid Amphipoda in the Gulf of California. Ph. D. Thesis, University of Arizona, Tucson, Arizona, 535 pp."]}